Structure and Well-Being of Incomplete Families in Russia. Issue 2 (3rd March 2016) - Churilova, E.V.
Abstract : Based on data from three waves of research, "Children and Parents, Men and Women in Family and Society" (CPMW) analyzed various aspects of the lives of incomplete families in Russia: their structure, well-being, and possibilities for single mothers to combine work and child care. The analysis showed that the household structure under single mothers tends to change over time: the number of relatives living together decreases. The housing conditions for single-mother families does improve, but improvement of their consumption ability and material circumstances does not last over time.